Elephant Back Safari Tourism in Sri Lanka: A Critique - Samarathunga, W.H.M.S. (Centre for Asian Studies, University of Kelaniya, Sri Lanka, 2016)
Elephant tourism in Sri Lanka dates back to the British period where the British rulers used to hunt down elephants as a sport (gaming tourism). Also, in ancient Sri Lanka, elephants were kept in captivity for centuries for domestic purposes including transportation and religious activities. Tourism has become a key contributor to the modern development of Sri Lanka. Thus, the authorities are looking at alternative modes in promoting Sri Lanka tourism to maximize economic returns. Elephant Back Safari (EBS) tourism is one of the popular tourist activities in Sri Lanka which has a significant demand among tourists. The problem central to this study revolves around this scenario. This paper examines the case of EBS tourism in both Pinnawala and Habarana tourist destinations. Observations, interviews and discussions were the primary data collection tools for this study. Descriptive writings were used to analyze the findings. Whilst tourists have mixed feelings about EBS tourism in general, they do not mind having a ride on the largest animal on the land. For many tourists an elephant ride is a "must to do" when they visit Asia. Although EBS has been regularized in Sri Lanka most of the operators do not fully adhere to the conditions. For example, the number of passengers often exceed the permitted number, the elephant sheds are not well kept and elephants who are not fit for the task are used in EBS. Also, the ways elephants are trained, fed and looked after, qualifications of the mahouts, lack of trained elephants and lack of information available are cause for great debate and concern in promoting EBS in Sri Lanka. However, the increasing international tourists’ demand for EBS keep this industry ever growing. Consequently, anthropologists, economists, environmentalists, and sociologists must develop a better framework to develop Sri Lankan EBS sector in a sustainable manner.
Keywords: Elephant Back Safari; tourism; sustainable tourism; tourist destinations; mahouts